Anti-Corruption Strategies in Jakarta Provincial Government: Educational, Preventive and Represive Approaches - Rahman, Dedy; Falatehan, A. Faroby; Hardiyanto, Arief Tri (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. Anti-corruption programs are the government's efforts to minimize the risk of corruption within the bureaucracy. However, implementing anti-corruption strategies often faces challenges, including the lack of coordination between the approaches used. Educative, preventive, and repressive approaches are often not well-coordinated, thus affecting the success of these anti-corruption programs. Therefore, this research evaluates the effectiveness of educational, preventive, and repressive programs implemented by the Jakarta Provincial Government in combating corruption, as measured by the Corruption Control Effectiveness Index (IEPK) through the Nvivo 14 Method. The study reveals that eight final verdict corruption cases occurred between 2017 and 2023, with seven of these cases arising before implementing the IEPK assessment model. Notably, the IEPK value improved from 2.94 in 2022 to 3.28 in 2023, indicating a shift from a